Penerapan Model Problem-Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa pada Materi Eksponen - Rafika Nur Azizah; Yatha Yuni; Andy Ahmad (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Mathematical problem-solving ability is one of the important competencies that need to be developed in mathematics learning. However, learning that is still dominated by conventional approaches can cause students to be less active in analyzing and solving mathematical problems. This study aims to improve the mathematical problem-solving ability of grade IX students of MTs Nurul Huda Rumbut Depok through the application of the Problem-Based Learning (PBL) model on exponent material. This study uses the Classroom Action Research (CAR) method which is implemented collaboratively in two cycles. Each cycle includes the planning stage, action implementation, observation and evaluation, and reflection. Data were collected through problem-solving ability tests consisting of an initial test, cycle I test, and cycle II test, as well as observation sheets for teacher and student activities. The success of the action was determined based on the implementation of learning of at least 80% and at least 80% of students obtaining a minimum score of 75. The results of the study indicate that the application of PBL improves students' mathematical problem-solving ability on exponent material and meets the research success criteria. Thus, the PBL model can be used as an alternative learning method to improve the mathematical problem-solving ability of grade IX students of MTs Nurul Huda Rumbut Depok